Let
. Then
![{y_2}'=tv'+v](https://img.qammunity.org/2020/formulas/mathematics/college/7x9gv7aioxqlcqhfrafzhitbm57a98tuiu.png)
![{y_2}''=tv''+2v'](https://img.qammunity.org/2020/formulas/mathematics/college/mvqhio4p2lhkq7oojfbwygso4vtbqolywd.png)
and substituting these into the ODE gives
![t^2(tv''+2v')+3t(tv'+v)-3tv=0](https://img.qammunity.org/2020/formulas/mathematics/college/gdqvizg6z66nsh30u41t8127ollmuidepe.png)
![t^3v''+5t^2v'=0](https://img.qammunity.org/2020/formulas/mathematics/college/vzvhxqiqahfbgbkhx3hztqztnq2zzna5gx.png)
![tv''+5v'=0](https://img.qammunity.org/2020/formulas/mathematics/college/xqihb4ko83qmze4s10atgd1k69c1y07h94.png)
Let
, so that
. Then the ODE is linear in
, with
![tu'+5u=0](https://img.qammunity.org/2020/formulas/mathematics/college/8lk277hsfrgapri5zfsy486x13tveyqq7i.png)
Multiply both sides by
, so that the left side can be condensed as the derivative of a product:
![t^5u'+5t^4u=(t^5u)'=0](https://img.qammunity.org/2020/formulas/mathematics/college/5d7qrlbp8eiibsqq2kefalt6ev6tps6rtq.png)
Integrating both sides and solving for
gives
![t^5u=C\implies u=Ct^(-5)](https://img.qammunity.org/2020/formulas/mathematics/college/pyd51d4k61wedhkatega4u9mu8jon3n01e.png)
Integrate again to solve for
:
![v=C_1t^(-6)+C_2](https://img.qammunity.org/2020/formulas/mathematics/college/qutaj5nt0riumow3793zq59kunyddsds87.png)
and finally, solve for
by multiplying both sides by
:
![tv=y_2=C_1t^(-5)+C_2t](https://img.qammunity.org/2020/formulas/mathematics/college/wt5ewbhuck4et7bmtlmi6cklwjuxfyaqnc.png)
already accounts for the
term in this solution, so the other independent solution is
.